Artificial Intelligence as a Source of Economic Success for Small Broiler Producers - Oliveira Filho, Aloísio Alkmim de (Anais do Encontro Unificado de Computação do Piauí (ENUCOMPI); 2022: Anais do XV Encontro Unificado de Computação do PiauíDO - 10.5753/enucompi.2022.222687, 2022)
The Brazilian poultry industry is one of the main sectors of agribusiness, being a strong sector in the South and Southeast regions, while in the North and Northeast the sector has not developed as much as the other regions. And one justification for this is the lack of technical assistance for producers in these regions. Thus, this work was justified to offer technical assistance to small poultry producers who carried out artificial incubation, through a chatbot. The result of using the chatbot was positive, since the producers had an increase in their production and a reduction in costs and inputs.